Maqui berry extract prevents cigarette smoke induced oxidative stress in human osteoblasts in vitro - Zhu, Sheng (EXCLI J, 2021)
Oxidative stress which can be induced by cigarette smoke (CS) is associated with an altered osteoblast differentiation, and an inhibition of the mineralization process. Therefore, treatments focusing on reducing oxidative stress in osteoblasts could be a potential therapy supporting bone formation. Maqui berry extract (MBE) is the richest natural source of delphinidins with high antioxidant activity. In the present study, we pre-/ co-/ post-incubated MBE in cigarette smoke extract (CSE)-affected human osteoblasts (hOBs), to investigate the effects of MBE as an antioxidant on hOBs. Our results clearly showed that high concentrations of MBE are toxic for hOBs, while physiological concentrations of MBE have no negative effects in vitro. Physiological concentrations of MBE can reduce oxidative stress caused by CSE in hOBs by activating the antioxidative regulator Nrf2 and its regulated antioxidative enzymes. Moreover, the physiological concentration of MBE prevents the detrimental effects of CSE-induced oxidative damage on hOBs by increasing cell viability, differentiation capability and matrix mineralization. Pre-incubation with MBE showed a positive effect on the activation of the cellular antioxidant system in hOBs. Thus, we conclude that MBE at physiological concentrations can effectively protect osteoblasts from oxidative stress-induced damage by activating the cells' antioxidative defense system.